Optimization of 2-phenylcyclopropylmethylamines as selective serotonin 2C receptor agonists and their evaluation as potential antipsychotic agents - Cheng, J.; Giguère, P.; Onajole, O.; Lv, W.; Gaisin, A.; Gunosewoyo, Hendra; Schmerberg, C.; Pogorelov, V.; Rodriguiz, R.; Vistoli, G.; Wetsel, W.; Roth, B.; et al. (American Chemical Society, 2015)
The discovery of a new series of compounds that are potent, selective 5-HT2C receptor agonists is described herein as we continue our efforts to optimize the 2-phenylcyclopropylmethylamine scaffold. Modifications focused on the alkoxyl substituent present on the aromatic ring led to the identification of improved ligands with better potency at the 5-HT2C receptor and excellent selectivity against the 5-HT2A and 5-HT2B receptors. ADMET studies coupled with a behavioral test using the amphetamine-induced hyperactivity model identified four compounds possessing drug-like profiles and having antipsychotic properties. Compound (+)-16b, which displayed an EC50 of 4.2 nM at 5-HT2C, no activity at 5-HT2B, and an 89-fold selectivity against 5-HT2A, is one of the most potent and selective 5-HT2C agonists reported to date. The likely binding mode of this series of compounds to the 5-HT2C receptor was also investigated in a modeling study, using optimized models incorporating the structures of β2-adrenergic receptor and 5-HT2B receptor.